G-quadruplexes catalyze protein folding by reshaping the energetic landscape - Zijue Huang; Kingshuk Ghosh; Frederick Stull; Scott Horowitz (Proceedings of the National Academy of Sciences, 2025)
Many proteins have slow folding times in vitro that are physiologically untenable. To combat this challenge, ATP-dependent chaperonins are thought to possess the unique ability to catalyze protein folding. Performing quantitative model selection using protein folding and unfolding data, we here show that short nucleic acids containing G-quadruplex (G4) structure can also catalyze protein folding. Performing the experiments as a function of temperature demonstrates that the G4 reshapes the underlying driving forces of protein folding. As short nucleic acids can catalyze protein folding without the input of ATP, the ability of the cell to fold proteins is far higher than previously anticipated.